Kajian Bentuk, Fungsi dan Makna Pakaian Sanak Butino dalam Acara Kenduri Sko di Kecamatan Gunung Kerinci - Resiana, Zelin; Pebriyeni, Eliya (AHKAM, 2025)
This study was aimed to identify and find out how the form, function and meaning of Sanak Butino traditional clothing worn at the Kenduri Sko event in Gunung Kerinci Sub-district. Type of research used was qualitative research with descriptive approach, using interview techniques with informants were several of Sanak Butino in Gunung Kerinci Sub-district. Based on research result, it is known that Sanak Butino traditional clothing consist of several parts, namely baju teluk balango, terap songket, selendang, kuluk/sungkun, tirai pabung, bungo aut, and jangki/bakun. The function of this traditional clothing as the identity of a Sanak Butino. In this traditional clothing there are meaning about social life values based on customary and religious law.